TEXT OF THE MYTH BULU GELES IN THE VILLAGE OF TAMBAKAN, KUBUTAMBAHAN DISTRICT, BULELENG REGENCY - Puspawati, Luh (e-Journal of Linguistics, 2015)
Tambakan Village Community, District Kubutambahan, Buleleng believe the tradition of myth sampi bulu geles text contained in that village that vows payment using calf ( bulu geles ) as offerings at Pura Dalem. Text tradition believed myth sampi bulu geles existence for generations. Currently not only Tambakan villagers who professed and offer bulu geles , but is also done by people from outside the village of Tambakan. This text of myth bulu geles tradition passed down from older generations to younger generation until now. Text of myth bulu geles contain bulu geles, I dewa offering. This kind of offering appear when troops from Buleleng kingdom and padanguah people lost in battle with Bangli kingdom and hide beneath the forest in Belong area. Belong area is the origin of Tambakan Village. The kind of this research is qualitative with source of primary and secondary data. Data is collected using observation, interview, and literature study technique. Text of myth Bulu geles tradition need to reviewed because this text of myth is unique and the review is focused in four matter there are first the structure of text of myth bulu geles in Tambakan Village? Second text of myth bulu geles in Tambakan Village function? Third text of myth bulu geles in Tambakan Village meaning? Fourth the bequeathing system of text of myth bulu geles in Tambakan Village? In term of issues reviewed, function, semiotic, and transmission theory are used. The result of the analysis gained that text of myth bulu geles in Tambakan Village has a narrative structure that is straight plot, primary and secondary figure, contain offering theme with place and time background. The sequence of ceremony in text of myth bulu geles in Tambakan Village that is cow release ceremony, calling process, catching and ended with bulu geles slaughter in mungkah wali ceremony. The function text of myth bulu geles in Tambakan Village that connected with context consist of rite function, social function, Tri Hita Karana function, and education function. The meaning of text of myth bulu geles in Tambakan Village is religious increasing meaning, prosperity meaning, unity and solidarity meaning, and heritation meaning. The bequeathing system of text of myth bulu geles in Tambakan Village is done by oral through word from old generation to younger generation hereditary that consist of environtment preservation, culture value preservation, and social preservation
Keywords: bulu geles, i dewa, mapanauran, mungkah wali